ANALISIS PAJAK, KEPEMILIKAN ASING, MEKANISME BONUS, PROFITABILITAS DAN PENGARUHNYA TERHADAP TRANSFER PRICING: Tax, Foreign Ownership, Bonus Mechanism, Profitability, Transfer Pricing - Hendrianto, Samino (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2022)
His study aims to analyze taxes, foreign ownership, bonus mechanisms, profitability and their effect on transfer pricing. The research time period used is 4 years, namely the 2017-2020 period. The population in this study are food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. The sampling technique used purposive sampling technique. Based on the predetermined criteria obtained 10 companies. The hypothesis testing used is Panel Data Regression Analysis using E-views 9.0 software. The results show that taxes, bonus mechanisms, and profitability have no effect on transfer pricing. Meanwhile, foreign ownership has a negative effect on transfer pricing.